1992
DOI: 10.5144/0256-4947.1992.63
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasites Among Food Handlers in Al-Medinah

Abstract: Fecal specimens from 13,216 food handlers (male) adults, representing 21 different nationalities, were analyzed for the presence of intestinal parasites at King Abdul Azeez Hospital, Al-Medinah. Approximately 14% of these individuals harbored potentially pathogenic parasites, the most common organism being Gicirdia lamblia (33%), followed by Entamoeba histolytica (23%), Trichuris trichiura (12.3%), Ascaris lumbricoides (11.8%) and others. The highest incidence of parasitic load was found in Sri Lankans (40.7%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Helminithic infection represented 46.67% of the total detected parasites. Nematoda infection with hookworms, T. trichiura and A. lumbricoides were the most common, as found in other studies [4,[7][8][9] . E. vermicularis adult female pinworm was isolated from a Bangladeshi food handler; same result was found in a Jeddah study [4] , but scanty eggs for this parasite were detected in stool as pinworms usually lay eggs in perianal region and not while in their habitat in the intestine.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Helminithic infection represented 46.67% of the total detected parasites. Nematoda infection with hookworms, T. trichiura and A. lumbricoides were the most common, as found in other studies [4,[7][8][9] . E. vermicularis adult female pinworm was isolated from a Bangladeshi food handler; same result was found in a Jeddah study [4] , but scanty eggs for this parasite were detected in stool as pinworms usually lay eggs in perianal region and not while in their habitat in the intestine.…”
Section: Discussionsupporting
confidence: 63%
“…On the other hand, two Yemeni and one Egyptian food handlers were infected with the dwarf tapeworm, which can easily cause both external and internal autoinfection. In an earlier study, in 1992, it was investigated the prevalence of intestinal parasites among 13216 male food handlers in King Abdulaziz Hospital in Al-Madinah [7] . The investigators found that approximately 14% of these individuals were infected with pathogenic parasites.…”
Section: Discussionmentioning
confidence: 99%
“…5 As most of these expatriate working as food handlers, baby sitters and domestic helpers hail from parasitic endemic countries, there are possibilities for them to carry them as asymptomatic carriers and to transmit them. [6][7][8] In contrast to protozoan infections, the prevalence of helminthes infections in our study was significantly low (8%) and it was mainly seen in expatriate population. Similar observations have been made in studies performed in the neighboring countries.…”
Section: Discussionmentioning
confidence: 76%
“…In the western region of Saudi Arabia, Entamoeba histolytica was found in 9.6% of the stool samples examined, followed by Giardia lamblia at 4.5% [17]. A study recently conducted by Ali et al [8] in Medina demonstrated that approximately 14% of 13,216 individuals harbored potentially pathogenic parasites in which the most common parasite was Giardia lamblia (33%) and the highest incidence of parasitic load was found to be among Sri Lankans (40.7%) [18]. In the present study, we obtained a relatively low prevalence rate of intestinal parasites among expatriates working in the UAE when the results were compared with the expatriates' home countries [6][7][8]12].…”
Section: Discussionmentioning
confidence: 99%